ANALYSIS OF ENVIRONMENTAL COMMUNICATION IN GARUT - Asha Tri Handayani; Heri Hendrawan; Feri Purnama (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Industrial growth in Garut City has exacerbated the problem of hazardous waste management. This study examines CSR communication in building environmental legitimacy when sustainability claims conflict with on-the-ground practices. The study employs legitimacy theory and a qualitative approach; The data were analyzed using Norman Fairclough's Critical Discourse Analysis (CDA) method, with analysis conducted on texts, discursive practices, and social practices in the field. Data collection involved observation, documentation, and in-depth interviews with environmental practitioners, activists, local leaders, WALHI, and the Garut Environmental Agency (DLH). The findings reveal that companies project an eco-friendly image through CSR and administrative compliance to secure social acceptance. However, weak oversight, symbolic CSR, and suboptimal waste management persist, indicating greenwashing practices. The novelty of this study lies in its examination of CSR communication as an environmental legitimacy strategy, a topic rarely explored in small cities like Garut. This research contributes methodologically through the integration of CDA procedures, empirically reveals the gap between rhetoric and local practices, and practically offers insights for CSR oversight policies.